Human Performance Optimization: A Framework for the Military Health System. (6th March 2023) - Travis, Thomas W; Brown, David L
ABSTRACT: The Department of Defense (DoD) is increasingly dependent on highly technological weapon systems, but the human is still at the heart of our war-fighting efforts. In order to maintain an effective fighting force, we must optimize and sustain human performance, which is defined as the successful completion of a specified task within an available performance capacity that meets or exceeds the mission demands. When health and performance are optimized and sustained, the costs of warfighter care and disability compensation are reduced and the quality of life is enhanced. Therefore, we propose that the Military Health System (MHS) reshape its focus on disease and injury treatment and prevention to embrace health enhancement for optimal human performance in a technology-rich battle space. This commentary develops a high-level strategy and policy framework to enable the MHS to optimize health and human performance for all DoD warfighters. We conducted a review of human performance literature, assessed existing health programs across the services, and conducted interviews with MHS and Line representatives. We found that the MHS has thus far met warfighter needs in a haphazard fashion. We propose an orchestrated approach to warfighter health and performance across the DoD and a more substantial partnership between Total Force Fitness and the MHS. We provide a notional concept for how the parts of this system could interact and a strategic framework for the delivery of health and performance to the warfighter.